(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In article it is considered researches of a role of ecological factors in formation of various diseases among the population of Karakalpakstan. Statistically significant dependence of a disease of respiratory organs on group of impurity is revealed.